Contribution of the arm segment rotations towards the horizontal ball and racket head velocities during forehand long shot and drop shot services in table tennis - Ibrahim, N.; Abu Osman, N. A.; Mokhtar, A. H.; Arifin, N.; Usman, J.; Shasmin, H. N. (Sports Biomechanics, 2022)
Service is assumed important in table tennis because an effective service may allow the serving player to control over the game; hence, the aim of this study was to determine the contribution of arm segment rotations towards ball impact during forehand service. Sixteen shake-hand grip collegiate table tennis athletes had participated in the study. It was revealed that by increasing the radial deviation angular velocity will increase the ball and racket velocities during drop shot service. Furthermore, it was revealed that increasing the wrist palmar flexion and radial deviation will enhance the racket velocity at impact during long shot service. However, it was recommended to the players not to concern on racket speed and arm segment rotations during contact phase as it could not accelerate the ball at impact during long shot service. Although it was the same forehand service, different length of flight ball lead to different contributions of arm segment rotations towards ball impact. The present findings highlight several better postures to increase racket and ball speed at impact during forehand long shot and drop shot services among advanced and intermediate players. Other ranked players may find this study useful as a fundamental understanding on kinematics serving arm.